Stunting was not associated with overweight among children aged 24-59 months - Adityas Afifah Hidayati; I Made Alit Gunawan; Bunga Astria Paramashanti (Alma Ata University Press, 2017)
ABSTRACTBackground: Stunting was associated with cognitive development, morbidity and productivity in later life. Several studies and analysis also showed that stunting was related to overweight. In Indonesia, prevalence of stunted-overweight in children was 7.4% in 2007, then increased to 7.6% in 2010.Objective: To understand the relationship between stunting and overweight among children aged 24-59 months.Methods: Cross-sectional design was used in this study. Study location was Sedayu Subdistrict, Bantul District. Participants were a total of 185 children selected by probability proportional to size (PPS) sampling technique. Main variables included nutritional status of stunting, overweight, and energy, protein and fat intakes. Analysis used was chi-square test with the level of significance 0.05.Results: The prevalence of stunting was 30.8%, whereas overweight prevalence was 10.3%. Bivariate analysis indicated that there was no significant relationship between stunting and overweight among children aged 24-59 months (OR= 1.3; 95%CI: 0.5-3.6). Energy, protein and fats intakes were not confounding variables, but effect modifier in the association between stunting and overweight.Conclusion: There was no relationship between stunting and overweight in children aged 24-59 months.KEYWORDS: stunting, overweight, children